Cấu trúc việc làm và suất sinh lợi từ vốn con người tại vùng kinh tế trọng điểm phía Nam - Võ Thành, Tâm; Huỳnh Ngọc, Chương; Huỳnh Thị Ái, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Human capital has long been considered an important resource of enterprises, including many components in which formal training and accumulated skills are considered the most important. Human capital return is a concept measured by the profitable values created by human capital for businesses. This study used the Heckman model to estimate and analyze the rate of return on human capital in the southern key economic region of Vietnam using the 2020 Vietnam Labor Force Survey (LFS) dataset with 49,207 observations after selection. According to the research findings, the rate of return connected with worker human capital, boosting the expansion of human capital in all aspects encourages a greater level of profitability.